2008
DOI: 10.1007/s11060-008-9721-3
|View full text |Cite
|
Sign up to set email alerts
|

A role for the p53 pathway in the pathology of meningiomas with NF2 loss

Abstract: The neurofibromatosis 2 locus (NF2) is inactivated through mutation and loss of heterozygosity (LOH) in 40-65% of all sporadic meningiomas, while the role of the p53 tumor suppression pathway in meningioma initiation and progression is still unclear. This study aims to determine if a p53 codon 72 arginine-to-proline polymorphism, found to be correlated with cancer development and cancer patient survival in other tumors, is associated with sporadic meningioma initiation or progression. We investigated Pro72 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
(47 reference statements)
0
22
0
Order By: Relevance
“…Recently, it was demonstrated that other pathways are associated with merlin, including p53/p21 signaling (1921). There are similarities between merlin and p53, such as that merlin functions as a general tumor suppressor product to multiple cell types as p53 does, and notably, their tumor suppressive functions are associated with cell cycle control (2527).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that other pathways are associated with merlin, including p53/p21 signaling (1921). There are similarities between merlin and p53, such as that merlin functions as a general tumor suppressor product to multiple cell types as p53 does, and notably, their tumor suppressive functions are associated with cell cycle control (2527).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our finding, several recent IHC studies of large cohort of human schwannomas and meningiomas that have detected elevated p53 expression in the majority of NF2 tumors (Chen et al, 2014; Pavelin et al, 2014). Moreover, p53 mutations and loss of p16 have both been linked to progression in human meningiomas (Chang et al, 2009; Kim et al, 2014). While it is tempting to speculate that Rac1-ROS-p53-driven checkpoints and senescence programs may also underlie the benign nature of NF2, it needs to be confirmed using disease relevant mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…thus, this study reveals a high degree of concordance in the aberrations of the p14ARF/MDM2/p53 pathway with the development of sporadic vestibular schwannomas. mesothelioma [4,19,20]. Studies on schwannoma development in patients suggest that a third hit in addition to the alteration of the NF2 gene may be necessary for the development of this tumor [18,24,25].…”
Section: Introductionmentioning
confidence: 99%